Quality and nutritional properties of pasta products enriched with immature wheat grain. (August 2013) - Casiraghi, Maria Cristina; Pagani, Maria Ambrogina; Erba, Daniela; Marti, Alessandra; Cecchini, Cristina; D'Egidio, Maria Grazia
<x xml:space="preserve">Abstract</x> In this study, nutritional and sensory properties of pasta enriched with 30% immature wheat grain (IWG), a natural source of fructo-oligosaccharides (FOS), are evaluated. Colour and cooking quality, nutritional value and glycaemic index (GI) of pasta were assessed in comparison with commercially enriched inulin and 100% wholewheat pastas. IWG integration induced deep changes in colour, without negatively affecting the cooking quality of pasta, and promoted nutritional quality by increasing the fibre content; IWG pasta presented a remarkable leaching of FOS in cooking water, thus providing only 1 g of FOS per serving. IWG pastas showed a GI of 67 (dried) and 79 (fresh), not significantly different from commercial pasta products. IWG can be considered an interesting ingredient to obtain functional products 'naturally enriched' in FOS and fibre. Results about FOS leaching suggest that, in dealing with functional effects, the actual prebiotic content should be carefully considered on food 'as eaten'.